Separation‐Free Polyaniline/TiO2 3D Hydrogel with High Photocatalytic Activity. Issue 3 (26th November 2015) - Jiang, Wenjun; Liu, Yanfang; Wang, Jun; Zhang, Mo; Luo, Wenjiao; Zhu, Yongfa
Abstract : A polyaniline (PANI) hydrogel with 3D network nanostructure is synthesized by polymerizing aniline. TiO2 nanoparticles are located onto the 3D matrix of the PANI hydrogel. This PANI/TiO2 composite 3D hydrogel is efficient in removing organic contaminants owing to the synergistic effect of adsorption‐enrichment and the succedent in situ photocatalytic degradation. In this process, organic contaminant is first adsorbed and enriched onto the surface of the TiO2 nanoparticles through 3D network nanostructure of PANI hydrogel. The organic contaminant is then in situ degraded. The 3D network structured PANI/TiO2 composite hydrogel has the advantage of high reactivity in nano‐sized materials and possesses the characteristics of separation‐free in bulk materials, indicating that the composite hydrogel is ease of recycling. Overall, this work provides new insights into the fabrication of hydrogel‐based nanocomposite materials and facilitates their potential application for the synergistic removal of various aquatic pollutants in the field of water purification. Abstract : A separation‐free polyaniline/TiO2 3D hydrogel is synthesized by polymerizing conductive polymer monomer. The composite hydrogel is efficient in removing organic contaminants due to the synergistic effect of adsorption‐enrichment and the subsequent in situ photocatalytic degradation. This work provides new insights into the fabrication of hydrogel‐based nanocomposite materials and facilitates their potential application in the field of water purification.